Atribución de algunos rasgos de comportamiento en personajes hipotéticos de categorías de edad diferentes - Lerner Stein, Roberto (1987)
96 students of the Catholic University were questioned in a survey to predict the probability of ocurrence of 20 behavioral characteristics in the reaction of a hypothetic character in 22 situations. The character could be male or female and young, middle aged or old. No stercotypes independent of the situation were found. The existance of 3 characteristic groups were established. The necessity to consider with great care the role of situaciones and the particularities of the individuals - in future investigations - is discussed.